Optimization of Process Parameters in the Hole Sinking Electrical Discharge Micromachining of Ti-6Al-4V Thin Sheet - Porwal, Rajesh Kumar; Yadav, Vinod (Asian Review of Mechanical Engineering, 2013)
The paper describes the multi-objective optimization of hole sinking electrical discharge micromachining (HSEDMM) process considering material removal rate (MRR), tool wear rate (TWR), and hole taper (Ta) as objectives simultaneously. The micromachining parameters considered in the present work are gap voltage and capacitance of capacitor. Eighteen set of experiments are conducted as per L18 orthogonal array and these experimental results are used for further optimization. Optimal combination of process parameters is determined using grey relational analysis that employs grey relational grade as performance indexes. The principal component analysis is applied to evaluate the weighting values corresponding to each performance characteristics so that their relative importance can be properly and objectively described. Optimal combination of the process parameters for the multiperformance characteristics of the hole sinking electrical discharge machining has been found as; gap voltage 140V and 100 pF capacitance of capacitor.